Perfil de resistência a antimicrobianos de bactérias patogênicas isoladas em sistema de tratamento de água negra simulada - Santana, Ana Beatriz (Universidade Federal de São Carlos, 2023)
The discharge of untreated domestic sewage compromises water quality, leading to imbalance in receiving bodies and enhancing the influx of pathogenic microorganisms and antibiotic-resistant strains, thereby posing a significant public health problem. Therefore, the aim of this study was to assess the efficiency of removing total coliforms, Escherichia coli, Staphylococcus aureus, and Enterococcus spp., and to detect the presence of Salmonella spp. at different stages of a simulated blackwater treatment system. Additionally, it involved isolating and biochemically confirming bacterial strains (excluding total coliforms) and delineating the antimicrobial resistance profile of the isolates.The investigated system, situated at the Monjolinho Sewage Treatment Plant in São Carlos (SP), comprises an upflow anaerobic sludge blanket (UASB) reactor followed by a tubular photobioreactor. Weekly samples were collected from simulated blackwater (AN), UASB reactor effluent (RU), and tubular photobioreactor effluent (FT). Nine collections were performed in Experiment I (08/2018 to 10/2018), and eight in Experiment II (03/2019 to 06/2019).Serial dilution-based counting revealed a notable reduction in microbiological load throughout the treatment system. Compared to AN, the average reduction in RU was 91.1%, and 99.3% and 91.6% for FT concerning AN and RU, respectively. Predictive Salmonella spp. colonies were detected in 6, 4, and 5 samples of AN, RU, and FT, respectively. Additional tests and antibiograms of confirmed isolates were conducted: for E. coli, MAR (Multiple Antimicrobial Resistance) indices for AN, RU, and FT groups reached 0.16, with 67% of samples being sensitive to all tested antibiotics, displaying higher resistance to Ampicillin 10μg and Tetracycline 30μg; Enterococcus spp., with MAR indices not exceeding 0.11, and up to 77% of samples being sensitive to all antibiotics, exhibiting higher resistance to Tetracycline 30μg and Streptomycin 300μg; and Salmonella spp., where in Experiment I, only one RU sample showed resistance, and in Experiment II, RU and AN exhibited MAR indices of 0.20 and 0.05, respectively, with higher resistance to Ampicillin 10μg and Tetracycline 30μg.In conclusion, the UASB reactor proved to be an effective blackwater treatment, resulting in lower microbiological load and reduced resistance (except for Salmonella spp. results). The photobioreactor, in addition to microbiological load reduction, can recycle nutrients, preventing eutrophication of the water bodies to which the effluent is directed. Nevertheless, further tests on a larger scale are necessary to substantiate and better define the reduction in load from the UASB effluent, and especially to investigate whether the difference in resistance between UASB and photobioreactor effluents is significant.
Antimicrobial resistance profile of pathogenic bacteria isolated from simulated blackwater treatment system
Keywords: Tratamento de efluentes; Fotobiorreator tubular; Bactérias multidroga resistentes; Wastewater treatment; Tubular photobioreactor; Multidrug-resistant bacteria; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA